Development of Physics Learning Media based on Guided Inquiry Model to Improve Students' Concepts Mastery and Creativity - Susilawati Susilawati; Ahmad Hardjono; Christine P. Abo; Lalu Muliyadi (Journal of Science and Science Education, 2021)
This study aims to develop learning media based on guided inquiry models to improve students' concepts mastery and creativity in physics learning in senior high schools. The learning media in question is a ripple tank to explain the characteristics of a mechanical wave. Development research with the 4D model (define, design, development, dissemination) was conducted in this study, where the learning media developed met the criteria of validity, practicality, and effectiveness in improving students' concepts mastery and creativity. Evaluation of the learning media validity is carried out through a validation mechanism where the media is validated by 3 validators (media experts), while evaluation of the practicality and effectiveness of learning media through its implementation in class involves students in two schools in Mataram City - Indonesia. The results of the study show that the learning media with the guided inquiry model are valid, practical, and effective in improving students' concepts mastery and creativity in learning physics. The results of further studies are described in this article